Effect of coal moisture on particulate emission in a fixed bed combustion appliance - Erdöl, Nalan; Çalli, Lütfü; Okutan, Hasancan; Arisoy, Ahmet; Ekinci, Ekrem (Elsevier BV, 1999)
Abstract Effect of moisture on particulate emissions of a young peaty (Agacli) coal from Turkey is investigated in a 93 kW, half cyclindirical hot water boiler. The boiler was operated under primary and secondary loading conditions. Sampling was realised using an EPA-approved Andersen Universal Sampling system. Experiments were carried out for 15.33%, 21.40% and 38.70% moisture coals of Agacli and 19.90% moisture Agacli–South African mixture coals. From the experimental results it is found that the medium moisture resulted in highest particulate emissions.